Drama for People 'in the know': Television World Theatre (BBC 1957–1959) and Festival (BBC 1963–1964). Issue 1 (2nd January 2017) - Smart, Billy
Abstract : This article provides a survey of the pioneering BBC series of theatrical adaptations Television World Theatre (1957–1959), examining BBC production documentation and audience research to identify the institutional discourses that surrounded the making and transmission of these programmes. Recurrent arguments throughout the production of the series form a framework of institutional expectations within which classic theatrical plays were commissioned, made and presented for BBC Television. Having identified these questions (relating to audience address, populism, and the viability of creating a unified 'house style' across the diverse plays included in an anthology series), the article assesses the contemporary press discourse surrounding Television World Theatre before concluding with a consideration of how the experience of Television World Theatre affected expectations the next time that the BBC attempted a similar project in Festival (1963–1964).